2015
DOI: 10.5603/fm.2015.0053
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the fundus of the internal acoustic meatus — micro-computed tomography study

Abstract: The aim of this paper was to present micro-computed tomography (micro-CT) high resolution images of the fundus of internal acoustic meatus (FIAM) (Folia Morphol 2015; 74, 3: 352-358)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
(15 reference statements)
1
11
0
Order By: Relevance
“…SR analyses, using a maximal intensity projection, occasionally showed an identifiable vessel. This is in concordance with Kozerska and Skrzat ( 51 ), who found that it may relay a branch or the AVA. It was earlier shown that selective obstruction of the AVA may be associated with sudden vertigo ( 52 ) followed by positional vertigo.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…SR analyses, using a maximal intensity projection, occasionally showed an identifiable vessel. This is in concordance with Kozerska and Skrzat ( 51 ), who found that it may relay a branch or the AVA. It was earlier shown that selective obstruction of the AVA may be associated with sudden vertigo ( 52 ) followed by positional vertigo.…”
Section: Discussionsupporting
confidence: 92%
“…We recently identified a foramen in the TC ( 46 ). Kozerska and Skrzat ( 51 ) identified this foramen only in infant skulls and suggested that it transmits blood vessels to the vestibule or the superior vestibular nerve (SVN) via the AVA. They could not rule out that it may contain nerve fibers.…”
Section: Discussionmentioning
confidence: 99%
“…However, vessels could be identified nearer the fundus region. A bone channel was described in the lateral part of the TC (Kozerska & Skrzat, ; Schart‐Moren et al. 2017b).…”
Section: Discussionmentioning
confidence: 99%
“…However, vessels could be identified nearer the fundus region. A bone channel was described in the lateral part of the TC (Kozerska & Skrzat, 2015;Schart-Moren et al 2017b). It was thought to transmit blood vessels to the vestibule (V) or nerve branch and to the otolith organs.…”
Section: Nerve Anastomosesmentioning
confidence: 99%
“…The most important reason for this complexity is that the regions of anatomical structures should be well known [2,10,19]. Especially the detail created by µCT in bone tissue is used to distinguish between anatomical structures [5,11]. The quality of education can be increased, more realistic observations can be made, patient-specific approaches can be applied and new plans can be created with these 3D models [6,10,18,23].…”
Section: Introductionmentioning
confidence: 99%